The tao of travel enlightenments from lives on the road - Theroux, Paul. (Boston Houghton Mifflin Harcourt, 2011)
A collection of writings from Paul Theroux's fifty years of travel. Included are writings from other travelers such as Charles Dickens, Eudora Welty, Anton Chekhov, Ernest Hemingway and many others.
Maps on endpapers.
Includes bibliographical references and index.
Keywords: Travel -- Anecdotes; Travelers -- Anecdotes